2012
DOI: 10.1123/ijspp.7.3.251
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review on Heart-Rate Recovery to Monitor Changes in Training Status in Athletes

Abstract: Heart-rate recovery (HRR) can be defined as the rate at which heart rate declines, usually within minutes after the cessation of physical exercise. [1][2][3] The autonomic nervous system (ANS) regulates both the initial increase in heart rate after the start of physical activity and the decrease in heart rate immediately after physical activity ends. The ANS is composed of a parasympathetic and a sympathetic branch that operate in a reciprocal and inverse manner: An increase in heart rate is caused by an incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
152
4
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(192 citation statements)
references
References 49 publications
16
152
4
3
Order By: Relevance
“…Delayed recovery of HR after physical exercise has been found as a risk factor for different cardiac complications (Cole et al 1999;Nissinen et al 2003) and is also a predictor of the training status of athletes (Daanen et al 2012). Increased vagal activity has been suggested to be responsible for the fast decrease of HR during the first minute after exercise cessation (Imai et al 1994;Perini et al 1989).…”
Section: The Dynamics Of Hrv Immediately After Exercisementioning
confidence: 99%
“…Delayed recovery of HR after physical exercise has been found as a risk factor for different cardiac complications (Cole et al 1999;Nissinen et al 2003) and is also a predictor of the training status of athletes (Daanen et al 2012). Increased vagal activity has been suggested to be responsible for the fast decrease of HR during the first minute after exercise cessation (Imai et al 1994;Perini et al 1989).…”
Section: The Dynamics Of Hrv Immediately After Exercisementioning
confidence: 99%
“…Dobro je poznato da je bolja fizička kondicija usko povezana sa bržim oporavkom srčane frekvencije. To je posledica funkcionalne adaptacije srca usled redovne fizičke aktivnosti (3,(10)(11)(12)(13)(14). Oporavak srčane frekvencije se koristi i za praćenje treninga i procenu kondicije (15)(16)(17).…”
Section: Uvodunclassified
“…Oporavak srčane frekvencije se koristi i za praćenje treninga i procenu kondicije (15)(16)(17). Osim fizičke utreniranosti, oporavak srčane frekvencije nakon vežbanja zavisi i od drugih faktora: zamora, pola, uzrasta, pripadnosti etničkim grupama, vrste i načina vežbanja (12,14,(18)(19)(20). Ograničen je, međutim, broj podataka iz literature koji ilustruju razlike u dinamici srčane frekvencije u populaciji vrhunskih sportista koji se bave razlim tipovima sporta.…”
Section: Uvodunclassified
“…Post-exercise heart rate recovery (HRR) is not always recorded or monitored following exercise testing, this is despite the well-established associations of slow HRR with training status [10], cardiovascular disease (CVD) risk and mortality [8,9,19]. HRR has also been reported to be modified by the CHRM2 gene in sedentary and trained individuals [13].…”
Section: Introductionmentioning
confidence: 99%
“…However, other investigators found no difference in HRR reliability following submaximal and supramaximal exercise [1]. A recent review supports the use of HRR as a valuable tool to monitor changes in training status in athletes and less trained individuals, which would also encompass clinical populations, but they highlighted the need for the standardisation of HRR protocols [10].…”
Section: Introductionmentioning
confidence: 99%